PENGARUH PENGERASAN MATA GERGAJI TERHADAP BEBERAPA SIFAT PENGGERGAJIAN - Osly Rachman; Jamal Balfas (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
Fifteen mahogany and six agathis logs in fresh cut condition were sawn into boards by a band saw machine. Each wood species was sawn using three saw blades with different cutting edge hardness i.e. hand swaging, alternate stellite . tipping and full stellite tipping. Sawing properties recorded include power consumption, cutting rate and sawing productivity for each wood species and cutting edge hardness.The results of study showed that wood species had no significant difference in terms of power consumption and cutting rate. Meanwhile, sawing productivity of agathis was higher than mahogany.Furthermore, the cutting edge hardnes had significant effect on sawing properties. It is found that the saw blade with alternate stellite tipping reduced power consumption, and increased the cutting rate and productivity.